Self‐Assembly of Giant Unilamellar Vesicles by Film Hydration Methodologies. Issue 6 (12th March 2019) - Rideau, Emeline; Wurm, Frederik R.; Landfester, Katharina
Abstract: Self‐assembly of lipids or polymeric amphiphiles into vesicular structures has been achieved by various methods since the first generation of liposomes in the 1960s. Vesicles can be obtained with diameters from the nanometer to the micrometer regime. From the perspective of cell mimicking, vesicles with diameters of several micrometers are most relevant. These vesicles are called giant unilamellar vesicles (GUVs). Commonly used methods to form GUVs are solvent‐displacement techniques, especially since the development of microfluidics. These methodologies however, trap undesirable organic solvents in their membrane as well as other potentially undesired additives (surfactants, polyelectrolytes, polymers, etc.). In contrast to those strategies, summarized herein are solvent‐free approaches as suitable clean alternatives. The vesicles are formed from a dry thin layer of the lipid or amphiphilic polymers and are hydrated in aqueous media using the entropically favored self‐assembly of amphiphiles into GUVs. The rearrangement of the amphiphilic films into vesicular structures is usually aided by shear forces such as an alternative current (electroformation) or the swelling of water‐soluble polymeric supports (gel‐assisted hydration). Abstract : Film hydration methodologies are essential for the generation of solvent and additive‐free giant unilamellar vesicles as cell models . The hydration of the dry amphiphilic films into vesicular structures can be spontaneous (gentle hydration) or aided by shear forces such alternative current (electroformation) or the swelling of water‐soluble polymeric supports (gel‐assisted hydration).